Who gets what? The interactive effect of MPs’ sex in committee assignments in Portugal - Espírito-Santo, A. (2019)
This article investigates the role of key individual-level factors, namely expertise, seniority and preferences in women’s assignments to legislative committees. It focuses on Portugal and draws on biographical data on MPs in five elections until 2009 and interviews with 20 legislators in 2014. The results show that female and male MPs have a similar probability of being appointed to powerful and economic issue committees, but female MPs are more likely to be appointed to social issue committees regardless of expertise and seniority. Although this outcome might be the product of their own preferences, it is influenced by embedded gender norms.